IMPLEMENTING CLUSTERING TECHNIQUE TO FOSTER STUDENTS’ DESCRIPTIVE WRITING SKILL AT SMP NEGERI 17 MAKASSAR - Rahmat Nur; Hj. St. Haliah Batau; Muliati Muliati (THE ACADEMIC: ENGLISH LANGUAGE LEARNING JOURNAL, 2022)
The purpose of this study was to know the level of ability and interest of students class VIIl-7 of SMPN 17 Makassar in writing descriptive texts using clustering techniques. This study uses the method of description. The research subjects were students of class Vlll-7 SMPN 17 Makassar in the odd semester in the academic year 2021/2022 with a sample of 33 students. Data collection is done by giving the task of writing descriptive text. The research data collected through the test showed that the students' writing ability after the research was conducted, the students were more interested in using clustering techniques in writing descriptive texts. Based on the results of data analysis, it can be seen that the student's result is 50.27 then after getting treatment the student's pre-test score increases to 78.88 on the post-test. So it can be concluded that using the clustering technique can improve students' learning abilities in writing descriptive texts at SMP 17 Makassar.